2008
DOI: 10.1002/glia.20792
|View full text |Cite
|
Sign up to set email alerts
|

Calcium store‐mediated signaling in sustentacular cells of the mouse olfactory epithelium

Abstract: Sustentacular cells have structural features that allude to functions of secretion, absorption, phagocytosis, maintenance of extracellular ionic gradients, metabolism of noxious chemicals, and regulation of cell turnover. We present data detailing their dynamic activity. We show, using a mouse olfactory epithelium slice model, that sustentacular cells are capable of generating two types of calcium signals: intercellular calcium waves where elevations in intracellular calcium propagate between neighboring cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 40 publications
4
64
0
Order By: Relevance
“…The percentage of cells that responded to the inactive enantiomer was less than the 8.7% of the WIN-responsive cells that also responded to Ringer’s physiological solution application (68/781cells from 34 slices). This observation likely reflects a small number of cells that respond to mechanical stimulation or exhibit spontaneous changes in calcium (Furuya et al, 1993; Hegg et al, 2009). The CB1 receptor specific antagonist AM251 (5 μM) was superfused over olfactory epithelium slices for 5 minutes prior to and during WIN application.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage of cells that responded to the inactive enantiomer was less than the 8.7% of the WIN-responsive cells that also responded to Ringer’s physiological solution application (68/781cells from 34 slices). This observation likely reflects a small number of cells that respond to mechanical stimulation or exhibit spontaneous changes in calcium (Furuya et al, 1993; Hegg et al, 2009). The CB1 receptor specific antagonist AM251 (5 μM) was superfused over olfactory epithelium slices for 5 minutes prior to and during WIN application.…”
Section: Resultsmentioning
confidence: 99%
“…Olfactory epithelium slices were prepared, loaded with fluo-4 AM calcium indicator dye (Life Technologies/Invitrogen, Grand Island, NY) and imaged on an Olympus Fluoview 1000 laser scanning confocal microscope (Olympus, Center Valley, PA) as previously described (Hegg et al, 2009). Briefly, slices were placed in a laminar flow chamber (Warner Instruments, Hamden, CT) and perfused continuously with Ringer’s solution at a flow rate of 1.5–2.0 ml/minutes.…”
Section: Methodsmentioning
confidence: 99%
“…A previous report from dissociated OSNs suggests that this is the case, as I7 and M71 neurons exhibited higher rates of spontaneous activity than mOR-EG neurons (Reisert 2010). In addition to potential damage to the cilia and axons, dissociation of OSNs also removes olfactory cells from the surrounding sustentacular and microvillar cells, which potentially influence OSN firing rates (Hegg et al 2009(Hegg et al , 2010Ogura et al 2011). We therefore examined OSNs situated in their natural configuration in the intact olfactory epithelia (Fig.…”
Section: Spontaneous Activity Differs Among Osns Expressing Differentmentioning
confidence: 87%
“…The discrepancy in overall firing rates is likely attributed to the different preparations and recording configurations. In the intact olfactory epithelial preparations OSN cilia and axons remain relatively undisturbed in their natural configuration, whereas in dissociated preparations OSNs are isolated from surrounding sustentacular and microvillar cells, which may affect firing (Hegg et al 2009(Hegg et al , 2010Ogura et al 2011). It has been shown in perforated-patch recordings that OSNs in intact epithelium respond to their respective ligands 100% of the time (Grosmaitre et al 2006), while the yield in dissociated OSNs is appreciably lower, suggesting that the intact epithelial preparation keeps OSNs healthier and is more physiologically relevant.…”
Section: Discussionmentioning
confidence: 99%
“…63 Many findings suggest that sustentacular cells play an important role in the regulation of ORN homeostasis and proliferation including the discovery of tight junctions between sustentacular cells and ORNs and complex calcium signaling in mouse sustentacular cells. 31,46,64 SUS-1 and SUS-4 have been described as useful antibodies for labeling sustentacular cells in the rat. 65,66 Using electron microscopy, Pixley et al 67 found that 1F4, an immunoglobulin (Ig)M kappa monoclonal antibody, selectively labeled the microvilli of sustentacular cells and ductal cells of Bowman glands in the rat.…”
Section: Epitheliummentioning
confidence: 99%